Study guide and workbook to accompany International economics - Dunn, Robert M.; Ingram, James C. (New York ; Chichester : John Wiley and Sons, 1996)
This book is divided into two parts: International trade; International finance.
Keywords: Economics; International economic relations -- Problems, exercises, etc